Pelatihan Pengembangan Kesejahteraan Psikologis pada Anak Asuh di Panti Sosial - Wustari L. Mangundjaya; Tri Widyastuti (Departement of Mathematics Education, 2023)
Having human resources with the qualification of competent, independent and have high self-confidence is the hope of every nation. This condition makes The Government of Indonesia through Nawa Cita and Merdeka Belajar Kampus Merdeka (MBKM) program has a goal in developing the human resources of Indonesia to become human resources who are competent, moving forward, have high values and has a competitive advantage. This condition has not only applied for normal children but also for children who live in the orphanage house. The objective of this community engagement program is to develop psychological well-being of the children who live in the orphanage which located in East Jakarta, by exploring the concept with six dimensions namely: a) self acceptance; b) autonomy; c) positive relations with others; d) environmental mastery; e) goal setting; and f) personal growth. This training used the combination of lecturing, discussion, games, and exercises. The results of the evaluation showed that in general this training is beneficial (72.5% very useful and 27.5% useful). Moreover, participants stated that they love the environment of the training, which is enjoyable, with games. Meanwhile, they stated that they did not like the long duration of the whole day training.